Evaluation from the quality of life in the oral breathers patients - Popoaski, Cristiane; Marcelino, Taise de Freitas; Sakae, Thiago Mamôru; Schmitz, Larissa Martins; Correa, Luiz Henrique Locks (Arquivos Internacionais de Otorrinolaringologia, 2012)
Introduction: The oral breathing is a frequent symptom in childhood and has many alterations that compromise the child physical and cognitive development, negatively influencing from the oral breather, comparing her with the not oral breathers.Method: Cross sectional study, prospective with a sample from 71 patients from 4 to 17 years, being 39 mouth breathers attended by otorhinolaryngologists and 32 patients not mouth breathers as the control group, evaluated as the quality of life through a questionnaire.Results: The oral breathers presented more nasal problems, with the sleep and food, besides an greater average punctuation for snoring at night (p < 0,0001), when compared to the control group. The prevalence of night snoring in the patients oral breathers was of 87,2%. The high punctuation in the scale of answers meant a worst quality of life.Conclusion: The syndrome of the oral breather seems to be related to a negative impact in the quality of life, mainly for the nasal problems, with the sleep and eating. Future studies with the application of the same questionnaire have become needed for this to become as capable instrument of evaluation of the life quality from the patients in the matter.
Keywords: mouth breathing; quality of life; snore; pharyngeal tonsil; palatine tonsil